2014
DOI: 10.1017/s1053837214000364
|View full text |Cite
|
Sign up to set email alerts
|

Market Internalization of Externalities: What Is Failing?

Abstract: The usual internalization of externality 'by the market' can be thought of through two different exchange modes: competitive markets, with Kenneth J. Arrow ( 1969 ); or bargaining, with Ronald H. Coase ( 1960 ). Although, in both cases, 'externality' refers to a non-exchanged effect that produces suboptimalities, these authors are working with two different, implicit conceptions of externality, rooted in different analytical worlds and calling for different institutions-parametric prices for the former but no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 87 publications
(194 reference statements)
0
10
0
Order By: Relevance
“…In order to explain why markets are missing, Arrow introduces such transaction costs at the end of his (1969) paper. Then he changes his previous conception of failure which becomes relative (see Papandreou 1994 or Berta andBertrand 2014). Nevertheless, he did not mention the transaction costs issue in his presentation of externalities a few years later (Arrow and Hahn 1971).…”
Section: Iii2 Arrow's Illustration and Formalisationmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to explain why markets are missing, Arrow introduces such transaction costs at the end of his (1969) paper. Then he changes his previous conception of failure which becomes relative (see Papandreou 1994 or Berta andBertrand 2014). Nevertheless, he did not mention the transaction costs issue in his presentation of externalities a few years later (Arrow and Hahn 1971).…”
Section: Iii2 Arrow's Illustration and Formalisationmentioning
confidence: 99%
“…Since this study is limited to the Arrow-Debreu framework, it is restricted to an ideal world without transaction costs (for a discussion of the introduction of transaction costs in Arrow's and Coase's internalisation of externalities, see e.g., Berta and Bertrand 2014). It does not concern itself with the use of externalities in some important theoretical fields, especially in macroeconomics, the institutional approach and the theory of property rights.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For investors, company performance is a function of time, with past performance being the basis for estimating future profitability and returns to shareholders. It was not clear that there was a compelling need or urgency to 'internalise' externalities (e. g. Berta andBertrand, 2014, Nicolaus Tideman andPlassmann, 2010) and for those effects to be reflected in the financials (both ex ante and ex post). The company's response would be conditioned by the actions (or inactions) of competitors.…”
Section: From Shareholders To Stakeholders?mentioning
confidence: 99%
“…Although internalization of externalities was introduced with very positive intensions, group of authors opposed this by proclaiming internalization as " insufficient for solving externality problem" (van den Bergh & Grazi, 2010;Bithas, 2011;Berta & Bertrand, 2014;Weitzman, 2015). Authors found that in the real world where externalities exist, their internalization cannot lead to the sustainability due to specific form of externalities.…”
Section: Literature Reviewmentioning
confidence: 99%